Application of acoustic emission for damage classification and assessment of corrosion in pre-stressed concrete pipes. (August 2020) - Goldaran, Reza; Turer, Ahmet
Highlights: Pressure fluctuation of pipe is the effective way for detecting the passive damages. Mixed AE sources using the RA and AF values could be classified. Corrosion-induced hydrogen bubbles could be categorized using a specific AE pattern. Abstract: The present study describes the usage of the AE technique for detecting different types of damage in corrosion process with characterization of corresponding AE sources in pre-stressed concrete cylinder pipes. Firstly, several small-scale tests were implemented to specify the characteristics of AE sources including water absorption of concrete, hydrogen bubbles bursting and concrete cracks, as well as determining the appropriate sensors positions. Later on, a full-scale pre-stressed pipe was subjected to corrosion under both constant and variable pressure; aiming to detect and classify the mixed type of damage sources. The results indicated that using AE technique, all sorts of damage sources can be classified at any stage of pipe life-cycle.